Kiyoko Kamio Knapp - Adler, Libby (Columbia Journal of Gender and Law, 1999)
Under our federalist system, the axiom has it, family law resides within the province of the states. This article disputes that axiom and seeks to arrive at a more precise understanding of the relationship between federalism and family. In its 1995 decision in United States v. Lopez, the Supreme Court invalidated the Gun-Free School Zones Act, a federal statute criminalizing handgun possession in proximity to a school yard. When Congress passed the Gun-Free School Zones Act, the Court held, it exceeded its authority under the Commerce Clause. Defending the need to impose limits on the scope of congressional power, the Court explained: [U]nder the Government’s. . .reasoning, Congress could regulate any activity that it found was related to the economic productivity of individual citizens: family law (including marriage, divorce, and child custody), for example. Under the theories that the Government presents. . .it is difficult to perceive any limitation on federal power. . . Family law, in the Court’s view, is the area of law paradigmatically suited to state control. Congressional regulation of family would signal the falling of the final outpost of federalism. It would mean that the powers of Congress were no longer enumerated, but had devolved into plenary police powers-the very spectacle of completely centralized sovereign control against which the framers of the Constitution struggled.